Studentsâ Learning Through Teaching Creativity: Teachersâ Perception - Roya Roustaee Masoumeh Pourrajab4, Sara Kasmaienezhadfard Baharak Taleblo (Universitas Ahmad Dahlan, 2015)
AbstractDuring the last few decades educators and parents have focused on the special needs and abilities of children therefore creativity and solving problems in creative way is identified as a main factor in reaching high educational aims. This paper is a study based on the literature and previous research papers to explain studentsâ learning through teaching creativity, with regarding teachers perception. Researchers cannot study creativity by isolating individuals and their work from the historical and social environment in which they act. So teachersâ perspective about creativity can be effective in process of studentâs learning. The findings of this study show there are many definitions and concepts about creativity which they should be considered by teachers to improve studentsâ creativity.Keywords: studentsâ learning, creativity, teachersâ perception, creativity in education.